The scaling relations of early-type dwarf galaxies across a range of environments. Issue 4 (9th September 2015) - Penny, Samantha J.; Janz, Joachim; Forbes, Duncan A.; Benson, Andrew J.; Mould, Jeremy
Abstract: We present the results of a Keck-ESI study of dwarf galaxies across a range of environment: the Perseus Cluster, the Virgo Cluster, the NGC 1407 group, and the NGC 1023 group. 18 dwarf ellipticals (dEs) are targeted for spectroscopy, three for the first time. We confirm cluster membership for one Virgo dE, and group membership for one dE in the NGC 1023 group, and one dE in the NGC 1407 group for the first time. Regardless of environment, the dEs follow the same size–magnitude and σ–luminosity relation. Two of the Virgo dwarfs, VCC 1199 and VCC 1627, have among the highest central velocity dispersions (σ0  = 58.4 and 49.2 km s −1 ) measured for dwarfs of their luminosity ( M R  ≈ −17). Given their small sizes ( R e  < 300 pc) and large central velocity dispersions, we classify these two dwarfs as compact ellipticals (cEs) rather than dEs. Group dEs typically have higher mean dynamical-to-stellar mass ratios than the cluster dEs, with M dyn / M ⋆  = 5.1 ± 0.6 for the group dwarfs, versus M dyn / M ⋆  = 2.2 ± 0.5 for the cluster sample, which includes two cEs. We also search for trends in M dyn / M ⋆ versus distance from M87 for the Virgo Cluster population, and find no preference for dwarfs with high values of M dyn / M ⋆ to reside in the cluster outskirts dyn centre.